Design{h}ers : a celebration of women in design today. - Wong, Sauman; Lim, YuetLin; Wong, Katherine; Lee, Leanne (Hong Kong : Victionary, 2019)
Foreword / Roanne Adams -- 4 stories + 27 showcases. Real talk #01: Purpose + Passion = Power / Jessica Walsh @ Sagmeister & Walsh -- Carolina Cantante & Catarina Carreiras @ Studio AH-HA -- Louise Mertens -- Charry Jeon @ CFC -- Yu Qiongjie @ Transwhite Studio -- AWATSUJI design -- Eva Dijkstra @ Design by Toko -- Susanna Nygren Barrett @ The Studio -- Real talk #02: Finding positivity in persistence / Verònica Fuerte @ Hey -- Lotta Nieminen -- Olimpia Zagnoli -- Beci Orpin -- Shyama Golden -- Maricor/Maricar -- Jessica Hische -- Camille Walala -- Leslie David -- Real talk #03: To experiment is to evolve / Yu Yah-Leng @ Foreign Policy Design Group -- Roanne Adams @ RoAndCo -- Vanessa Eckstein @ Blok Design -- Elaine Ramos @ UBU -- Tina Touli -- Leta Sobierajski -- Lu Ihwa @ O.OO -- Real talk #04: The art of flowing fearlessly / Hattie Stewart -- Morag Myerscough -- Anna Kuts & Sevilya Nariman-qizi @ Razöm -- Sylwana Zybura @ CROSSLUCID -- Jess Bonham -- Birgit Palma -- Asuka Watanabe.
boek